PENGARUH KOMPETENSI, MOTIVASI, LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. “W” - Waruwu, Dicky Rahmat; Achmad, Nur (ITB AAS Indonesia Surakarta, 2024)
Employee productivity as an important thing in the company will be achieved with employees who have good competence in their respective fields of work. The purpose of this study is to determine the influence of competence on employee work productivity at PT. W, the influence of motivation affects the work productivity of employees at PT. W and the influence of the work environment affect the work productivity of employees at PT. W. This study uses a quantitative approach, a research method based on the philosophy of positivism, used to use research instruments, quantitative data analysis with the aim of testing the hypothesis that has been determined. Population is the number of employees in PT. W as many as 55 people. The result obtained by the competency variable (X1) is which means that the result has a significant effect on work productivity (Y). The motivation variable (X2) did not have a significant effect on work productivity (Y). The work environment variable (X3) had a significant effect on work productivity (Y).